Patterns of Care in the Administration of Neo‐adjuvant Chemotherapy for Breast Cancer. A Population‐Based Study. Issue 3 (4th March 2016) - Vugts, Guusje; Maaskant‐Braat, Adriana J. G.; Nieuwenhuijzen, Grard A. P.; Roumen, Rudi M. H.; Luiten, Ernest J. T.; Voogd, Adri C.
Abstract: Neo‐adjuvant chemotherapy (NAC) is used to facilitate radical surgery for initially irresectable or locally advanced breast cancer. The indication for NAC has been extended to clinically node negative (cN0) patients in whom adjuvant systemic therapy is foreseen. A population‐based study was conducted to evaluate the increasing use of NAC, breast conserving surgery (BCS) after NAC and timing of the sentinel node biopsy (SNB). All female breast cancer patients, treated in 10 hospitals in the Eindhoven Cancer Registry area in the Netherlands between January 2003 and June 2012 were included ( N = 18, 427). In total, 1, 402 patients (7.6%) received NAC. The administration increased from 2.5% in 2003 to 13.0% in 2011 (p < 0.001). Use of NAC increased from 0.5% to 2.3% for cT1 tumors, from 2.8% to 27.0% for cT2, from 30.6% to 70.9% for cT3, and from 40.5% to 58.1% for cT4 tumors (p < 0.001). In cN0 patients, use of NAC increased from 1.0% to 4.4% and in clinically node positive patients from 12.0% to 57.5% (p < 0.001). Downsizing of the tumor and BCS are achieved increasingly. In 2011, in three hospitals NAC was administered in <10% of patients, in five hospitals in 10–15% and in two hospitals the proportion of patients receiving NAC was >20% (p < 0.001). Of the 1, 402 patients with NAC, 495 patients underwent SNB, 91.5% of whom prior to NAC. In the Netherlands up to one in eight patients receive NAC. The administration of NAC and the percentage of BCS increased over the past decade, especially in cT2 tumors. Considerable hospital variation in the administration of NAC exists.